Creative Learning Based on 7 Habits of Great Indonesian Children to Improve Discipline and Independence in Learning - Tri Untari; Prahastiwi Danik; Rimba Maulana; Matari Ali (Institut Studi Islam Muhammadiyah (ISIMU) Pacitan, 2025)
This study aims to examine historically and theoretically the creative learning model based on the Seven Habits of Great Indonesian Children as an effort to improve children’s discipline and independence in learning. The concept of these seven habits is adapted from the theory of Seven Habits of Great Indonesian Children (SHGIC), which has been adjusted to the character values of the nation and the Pancasila Student Profile. Through a historical approach, this study traces the development of character education ideas in Indonesia and their relevance to current learning needs. The results of the study show that the application of a creative learning model based on the seven habits can naturally shape positive habits in children through habituation, role modeling, and meaningful play activities. This model is effective in fostering discipline, responsibility, and independent learning from an early age, while also supporting the creation of a humanistic and character-oriented learning environment.